Penerapan Asuhan Keperawatan pada Klien Isolasi Sosial dengan Pendekatan Model Konseptual Hildegard E. Peplau dan Virginia Henderson: Application of Nursing Care for Clients with Social Isolation Using the Conceptual Models of Hildegard E. Peplau and Virginia Henderson - Dewi Eka Putri (NERS Jurnal Keperawatan, 2012)
Social isolation is an individual ability degradation in having interaction with others due to interpersonal function disorder. This paper objective is to present implementation of nursing care for social isolation client through Social Skills Training (SST) by using Peplau and Henderson Nursing Theory. The Research taken place at RW 02 and 08 Katulampa Village. The Nursing Care treatment applies to 11 clients, 8 of whom were treated with SST. The clients who received SST therapy were able to manage social interaction and build interpersonal relations with others. Nursing Care at the community level needs support from the family and members of the community through Kader Kesehatan Jiwa (KKJ). This support will help clients maintain their ability to develop interpersonal relations. Peplau and Henderson theory approach makes it easier for nurses to develop interaction with Social Isolation clients, making SST Therapy more effective.